National Identity in the Indonesian Youth [Identitas Nasional di Kalangan Orang Muda Indonesia] - Augustinus Supratiknya (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2021)
National identity (identitas nasional [IN]) and ethnic identity (identitas suku bangsa [ISB]) as two forms of social identity are important to scrutinize in the multi-ethnic nation of Indonesia. This research comprised two studies and aimed to uncover the Indonesian youth’s national identity (identitas nasional [IN]) on a sample of male and female students with different backgrounds in ethnicity, religion, and identity source. Study 1 aimed to construct an instrument of youth’s national identity (identitas nasional [IN]) by adapting the Skala Identitas Suku Bangsa (SISB; 2019), resulting in the Skala Identitas Nasional (SIN) consisting of 12 items (rit = 0.35 -0.64; α = 0.84). Study 2 aimed to explore the participants’ national identity (identitas nasional [IN]; N = 480) by considering the differences of their backgrounds. The results showed that in general the participants’ level of national identity (identitas nasional [IN]) was high, especially on the Balinese and Florinese samples; their level of national identity (identitas nasional [IN]) correlated with their level of ethnic identity (identitas suku bangsa [ISB]); religion related with levels of national identity (identitas nasional [IN]) through its connection with ethnicity, hence the Hindu-Balinese sample indicated the highest; the majority of participants acknowledged the parents and the extended family as their source of identity, but seemed to fail in contributing to the formation of the youth’s national identity (identitas nastional [IN]); male participants showed a higher level of national identity (identitas nasional [IN]) than female participants. Possible causes of the important findings were discussed and follow-up research on those findings were recommended. Identitas nasional (IN) dan identitas suku bangsa (ISB) sebagai dua bentuk identitas sosial penting dicermati dalam masyarakat Bangsa Indonesia yang multi-etnik. Penelitian ini meliputi dua studi, bertujuan mengungkap identitas nasional (IN) orang muda Indonesia dengan sampel mahasiswa laki-laki dan perempuan berlatar-belakang suku bangsa, agama, dan sumber identitas berlainan. Studi 1 bertujuan menyusun alat ukur identitas nasional (IN) orang muda dengan mengadaptasi Skala Identitas Suku Bangsa (SISB; 2019), menghasilkan Skala Identitas Nasional (SIN) yang terdiri dari 12 butir (rit = 0.35-0.64; α = 0.84). Studi 2 bertujuan mengungkap identitas nasional (IN) partisipan (N = 480) secara eksploratif dengan memperhatikan perbedaan latar belakang mereka. Hasilnya, secara umum taraf identitas nasional (IN) partisipan cukup tinggi, khususnya pada sampel suku bangsa Bali dan Flores; taraf identitas nasional (IN) mereka berkorelasi dengan taraf identitas suku bangsa (ISB); agama berhubungan dengan taraf identitas nasional (IN) melalui hubungannya dengan suku bangsa, maka sampel Hindu-Bali menunjukkan taraf identitas nasional (IN) tertinggi; mayoritas partisipan mengakui orang tua dan keluarga besar sebagai sumber identitas, namun ada indikasi mereka kurang berperan dalam pembentukan identitas nasional (IN) orang muda; sampel laki-laki menunjukkan taraf identitas nasional (IN) lebih tinggi dibandingkan sampel perempuan. Kemungkinan penyebab temuan-temuan penting dibahas, dan saran untuk penelitian lebih lanjut dikemukakan.